Cooling Externality of Large-Scale Irrigation - Braun, Thomas,Schlenker, Wolfram (National Bureau of Economic Research, 2023)
We provide novel evidence that large-scale irrigation heterogeneously shifts the temperature distribution towards cooler temperatures during the months of the growing season relative to the rest of the year. We employ a triple-difference estimator using a 59-year-long panel of weather records paired with the fraction of a county that is irrigated in 393 counties over the Ogallala aquifer. Cooling-by-irrigation propagates downwind and reduces the upper tail of the temperature distribution by up to 3C (5F) during the month of August, which has positive externalities on downwind crop yields (120 million per year) and temperature-induced excess mortality (240 million per year) that are of equal magnitude as the direct benefits of irrigation by enhancing heat tolerance (440 million per year). The observed cooling helps explain why the US has seen less warming, especially of very hot temperatures, than what climate models project. Our findings highlight that weather shocks in highly irrigated areas are not exogenous but are influenced by human responses in the form of irrigation
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Bewässerung; Wetter; Klima; Pflanzenbau; Externer Effekt; USA; General; Land Ownership and Tenure; Land Reform; Land Use; Irrigation; Agriculture and Environment; Climate; Natural Disasters and Their Management; Global Warming